Los videojuegos: una herramienta comunicacional para sensibilizar sobre la pobreza en el sur - Wörmer Nixdorf, Nina (Revista Española de Desarrollo y Cooperación, 2023)
This article tries to demonstrate that some videogames can be used as an awareness tool that can show the South reality to the North youth. It will specially focus on seeing which videogames give information and make awareness about hunger and poverty in those countries. It tries to emphasize the important connections between society and videogames when these are seen as a media or an awareness tool.